Síntese e caracterização de nanopartículas de ouro conjugadas com curcumina e seus efeitos na osteoartrite experimental induzida - Campos, Wilma Neres da Silva (2017)
Osteoarthritis (OA) is the clinical term for a combination of pathological conditions that involve the progressive degeneration of articular cartilage and subchondral bone remodelling. Curcumin, a potent anti-inflammatory agent, has been extensively studied however, it does not provide good systemic bioavailability. Gold nanoparticles (AuNPs) have potential applications in the administration of therapeutic substances in order to increase the transport efficiency of drugs. The objectives of this study were to explore the synthesis and characterization of a system combining AuNPs with curcumin and evaluate its therapeutic potential in an experimental model of OA in mice by the destabilization of the medial meniscus (DMM). The AuNPs were conjugated with curcumin and the systems were characterized by UV-VIS spectroscopy, dynamic light scattering (DLS), and zeta potential. Four groups of eight animals each were formed and labelled A, B, C, and D, which received intra-articular injections of AuNPs, curcumin, AuNP-curcumin, and physiologic solution, respectively. After seven weeks, the cartilage of the stifle joint (SJ) was rated on a scale ranging from 0 to 24. The combination of AuNP curcumin showed good stability and therapeutic applications, but it did not differ significantly (p>0.05) from groups A and B. However, the control group had a significantly lower score (p <0.001). The results of this study show the importance of developing new nanodrugs. In this case, the combination of AuNPs and curcumin yielded the nanodrug effects suggestive of a potential for application in the treatment of OA.